1997
DOI: 10.1002/(sici)1099-1085(199705)11:6<627::aid-hyp481>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Suspended Sediment and Particulate Phosphorus Transport and Delivery Pathways in an Arable Catchment, Gelbæk Stream, Denmark

Abstract: Reliable quanti®cation of suspended sediment (SS) and particulate phosphorus (PP) transport, and identi®cation of the various delivery pathways at the catchment level, is an important and necessary aid to appropriate catchment management. In this study we measured storm event, seasonal and annual losses of SS and PP from a Danish arable catchment, Gelbñk Stream, using a multisampling strategy. SS losses for the study years May 1993±April 1994 and May 1994± April 1995 ranged from 71 to 88 kg ha À1 , while PP lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(144 citation statements)
references
References 16 publications
10
132
1
1
Order By: Relevance
“…Very few studies in Ireland have looked at soil erosion rates on tillage soils, despite international research by Kronvang et al (1997), , Deasy et al (2009), Stevens et al (2009) and Van Oost et al (2009) concentrating specifically on such soils due to their erosion propensity. The loss of fertile topsoil due to soil erosion on agricultural land is a growing problem in Western Europe, and has been identified as a threat to soil quality and the ability of soils to provide environmental services (Boardman et al 2009).…”
Section: Factors Affecting Soil Erosion Rates In Irelandmentioning
confidence: 99%
See 1 more Smart Citation
“…Very few studies in Ireland have looked at soil erosion rates on tillage soils, despite international research by Kronvang et al (1997), , Deasy et al (2009), Stevens et al (2009) and Van Oost et al (2009) concentrating specifically on such soils due to their erosion propensity. The loss of fertile topsoil due to soil erosion on agricultural land is a growing problem in Western Europe, and has been identified as a threat to soil quality and the ability of soils to provide environmental services (Boardman et al 2009).…”
Section: Factors Affecting Soil Erosion Rates In Irelandmentioning
confidence: 99%
“…Increasing eutrophication of many surface water bodies in arable regions of the UK has been linked with increasing rates of soil erosion causing sediment and P loss from fields cropped with winter cereals and with an accumulation of soil P through continuous application of fertiliser and manures (Catt et al 1998). Research to establish the circumstances leading to sediment and P losses from arable land and to quantify these losses has been carried out in the UK (Speirs and Frost 1987;Chambers et al 1992;Catt et al 1998; and throughout Europe (Kronvang et al 1997;Verstraeten and Poesen 2001;Miller and Quinton 2009) at multiple scales. Reported sediment and P losses from arable sites in these and other similar studies were significantly higher than losses from grassland, and were high enough to cause concern over the eutrophication of surface water bodies in arable areas.…”
Section: Introductionmentioning
confidence: 99%
“…Collins and Walling (2004) point out that, though it is difficult to acquire information about sediment entry pathways, it is important to understand sediment sources for deriving management plans and to prevent environmental problems. The main sediment entry pathways in lowlands are the input from agricultural drains, bank erosion and field erosion (Russel et al, 2001;Kronvang et al, 1997;Walling et al, 2002). Different criteria influence sediment input from these three sources: The sediment contribution from drains is highly variable and rarely researched.…”
Section: Introductionmentioning
confidence: 99%
“…It seems to be governed by factors like soil type, groundwater levels, soil moisture, drainage depth and age, land use, irrigation (Walling et al, 2002;Stone and Krishnappan, 2002) as well as the size of the drained area (Smith et al, 2005). While Kronvang et al (1997) and Stone and Krishnappan (2002) found sediment losses from drains of 20 to 130 kg ha −1 yr −1 , Ulèn and Persson (1999) and Chapman et al (2005) investigated drains under loamy and clayey soils with a high susceptibility to form macropores and measured extremely high values of up to 230 and up to 1000 kg ha −1 yr −1 , respectively. River bank erosion depends on water flow characteristics like depth and velocity, freezing and thawing processes, the soil type, soil density and moisture, vessel traffic, cattle treading, as well as stream properties like curvature, cross-sectional shape and plant cover (Hooke, 1979;Saynor et al, 2003;Laubel et al, 1999;Bradbury et al, 1995;Wynn et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the risk pose by rainfall events can be improve in the implemented risk model as long as rainfall intensity data are available. It should be stressed that large amounts of nutrients are flushed out from lands during a few heavy rainfall events [76]. This is particularly relevant when manure is applied and left exposed on the surface (splash-plate method).…”
Section: Resultsmentioning
confidence: 99%